Identification of Termites’s Hindgut Bacterial Symbionts (Coptotermes curvignathus Holmgren) and the Feasibility in Rice Straw Decomposting - Marheni Sembiring; Yunda Gusriani (Jurnal Perlindungan Tanaman Indonesia, 2019)
Cellulotic bacteria can be used as breakers of cellulose bonds in rice straw, one of which is cellulotic symbiont bacteria found in the hindgut part of termite Coptotermes curvignathus Holmgren. The study aimed to characterize and identify bacterial isolates from the back intestine of C. curvignathus termites and test the ability of bacterial isolates to decomposition rice straw. The results of isolation on worker caste termites found one bacterial species that was successfully cultured in Carboxylmethil Cellulose (CMC) media. Biochemical test results for isolates, showed that, bacteria found in rod form (rod shape), aerobic, gram negative, motile and produced catalase enzyme. Sequencing of 16S rRNA genes in bacterial isolates showed similarities with Bacillus cereus. A dose of 10 ml symbiont starter, 50% in concentration, applied to 2 kg rice straw can shorten the decomposition time from 12 weeks to 4 weeks, reducing the required decomposition time which is about 75% of the normal time.